Warehouse Modeling in Strategic Planning Model - Katias, Puspandam; Karya, Denis Fidita (UNUSA Press, 2019)
As a critical point in the supply chain, warehouse facility must be managed in good way, started from planning and design becomes important, this research using modeling tool to make and ensure the warehouse to be more effective and efficient. This paper to analyze the concepts of modeling for managing warehouse facility, from strategic level to operational level, for future re- search to provide a conceptual references also contribute to project management. The Problem in this analysis formulated as: 1). how modeling in designing and planning warehouse in action, and 2) how modeling in designing and planning warehouse as classified. The findings of this research with a modeling project: a model of classification for managing efficient warehouse, especially in strate- gic planning model.